ISLAM AND LOCAL CULTURE IN TIMOR - Bolong, Bertolomeus (Universitas Islam Indonesia, 2020)
Religious teachings come from Allah's revelation while culture is a human creation. However, religion and culture are two things that influence each other. Religious values and cultural values penetrate and shape the character of the community who adhere to them. This paper is a study of the life of Islam in East Nusa Tenggara Province in its interaction with local culture. Muslims in Timor who come from various ethnic and cultural backgrounds are people who are devout in practicing their religious faith. But on the other hand, they also stick to and obey their culture. In its embodiment, religion purifies culture and culture forms the character of society to be loyal to their religious faith.